Review of pre-treatments used in anaerobic digestion and their potential application in high-fat cattle slaughterhouse wastewater. (1st October 2015) - Harris, Peter W.; McCabe, Bernadette K.
Highlights: We review pre-treatment options applicable to wastewater high in fats and oils. The unique characteristics of abattoir wastewater are summarised. Pre-treatments are evaluated for their potential to improve anaerobic digestion. Appropriate pre-treatment technologies are considered on the basis of performance. Limitations and future research opportunities in this area are presented. Abstract: This paper explores pre-treatment options for the anaerobic digestion (AD) of high-fat cattle slaughterhouse wastewater by assessing and attempting to compare pre-treatment methods used to treat various waste streams. The central focus on cattle slaughterhouse wastewater stems from the problematic nature of high fat, oil and grease (FOG) present in Australian red meat processing (RMP) waste water. Fully integrated abattoirs such as those operating in Australia typically produce wastewaters that carry high FOG loads of 100–4000+ mg/L. While excessive levels of fat can be inhibitory to the AD process, these fats contain a very high theoretical methane potential of 1014 L CH4 /kg VS when compared with carbohydrates at 370 L CH4 /kg VS and proteins at 740 L CH4 /kg VS. However, due to the hydrophobic and inhibitory nature of fat, oil and grease, accessing this methane potential is difficult. This article serves as a review of the literature in the field of pre-treatment of wastewaters and subsequent anaerobic digestion with the goal of increasing biogas yield, with an emphasis on digestion of wastes high in fat, oil and grease. This review covers mechanical pre-treatments including high-pressure homogenisation, ultrasonication and electrokinetic disintegration, and other forms of pre-treatment including thermal, chemical, thermochemical, and enzymatic hydrolysis, and biochemical emulsification. Biological pre-treatments, also known as pre-hydrolysis and two stage digestion are briefly reviewed. The most significant considerations for selecting a pre-treatment technology are the energy balance and costs. Therefore, this review will also provide a commentary on the advantages and disadvantages of the pre-treatment methods reviewed and conclude by evaluating their relative worth in pre-treating FOG.